Effects of Port Site Bupivacaine Infiltration to Reduce Post Operative Pain in Laparoscopic Cholecystectomy: A Double Blind Randomized Controlled Trial (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: Laparoscopic cholecystectomy has become the treatment of choice for symptomatic gall stone disease. But post operative pain may prolong hospital stay and increase morbidity. The aim of the study was to find out the effect of port site infiltration of Bupivacaine in reducing post operative pain following routine laparoscopic cholecystectomy. Materials and methods: This is a double blind randomized controlled trial conducted in the Department of Surgery, Chittagong Medical College Hospital, Bangladesh. A total 200 patients underwent routine laparoscopic cholecystectomy were enrolled in the study. All patients are assigned in two groupscontrol group (Infiltration of 20 ml normal saline at port site) and Bupivacaine group (20 ml Bupivacaine at port site). Both groups are followed at 4 hrs, 12 hrs and 24 hrs after operation to assess the intensity of pain by using Visual Analogue Pain Scale (VAS). Time regarding the first analgesic request by the patients, total dose of analgesic, days of return to normal day to day activities and normal works were also recorded. Results: The mean age of control group and Bupivacaine group were 41.64 and 37.54 years respectively. At 4hrs post operative mean pain score were 6.76 and 5.62 respectively (p value 0.015). At 12 hrs mean pain score were 4.4 and 3.88 respectively (p value 0.001). At 24hrs pain score were 2.66 and 2.08 respectively (p value 0.002). Mean time of first analgesic required were 4.8hrs and 7hrs respectively (p value 0.000). Mean duration of hospital stay were 2.26 days and 2.22 days respectively (p value 0.371). Total dose of analgesic required were 12 and 9 between the groups respectively (p value 0.000). Mean time of return to normal day to days activities were 3.98 days and 2.98 days respectively (p value 0.000). Return to normal work after 6.98 days and 6.46 days respectively between the groups (p value 0.008) that is statistically significant. Conclusion : Infiltration of Bupivacaine at port site at post operative period of laparoscopic cholecystectomy patients significantly reduces pain than control group. It helps patients for early mobilization, early return to normal activities and works. Thus it reduces overall cost and morbidity of symptomatic cholelithiasis patients.JCMCTA 2017 ; 28 (2) : 64-68